Entrepreneurship in Green Energy: A Review - Agung Purnomo; Nur Afia; Elsa Rosyidah (Syntax Idea)
Entrepreneurship in green energy is highly required to ensure everyone can access energy, energy efficiency improvements, renewable energy sources, and increased public and private awareness. This paper attempts to review the body of knowledge and research on entrepreneurship in green energy. Using a systematic literature review of the PRISMA guidelines for conducting and reporting systematic reviews. Several peer-reviewed publications were included following a thorough search of the Scopus databases. The findings demonstrate several publications on entrepreneurship in green energy from the quantitative analysis and perspective analysis. The number of research-related publications each year on entrepreneurship in green energy has been an upward trend. The United States was the top research nation. The most intensive topics of green energy and entrepreneurial industry sectors were bioenergy and financial. This research provides information that has opportunities to be carried out, including research on entrepreneurship in the field of green energy, with the topic of marine energy, geothermal energy, and the health industry sector.